حفظ الأمن في الإسلام وأثره في البناء والتنمية - لعناني، عربية; بن صافى، حبيب Bin Safi, Habib (جامعة غرداية, 2020)
حفظ الأمن مقصد من المقاصد التي سعت الشريعة الإسلامية إلى تحقيقها، وهو غاية كل المجتمعات الإنسانية، ونعمة من النعم العظيمة التي امتن الله بها على عباده كما هو وارد في كثير من آي القرآن الكريم ونصوص السنة النبوية الشريفة، والذي ينبغي الحرص على تمكين موجبات دوامه، وتفعيل وسائل حفظه، فهو أساس البناء والتنمية وازدهار الحضارة، ومطلب جميع الخلق لما يتم من خلاله من تحصيل مصالحهم في الحال والمال.
The maintenance of security is one of the purposes that the Islamic charia sought to achieve, and is the objective of all human societies, and one of the greatest blessings that god grants his servants as it is shown in many verses of Quran and texts of the prophet’s sunna. Hence, it is necessary to work on keeping the seeds of its permanence, and activating the means of preserving it because it forms the basis for the constructin, development and prosperity of civilization, and it is a necessity for all people as it enables them to obtain their present and future interests.
Keywords: الحضارات الإنسانية -- التنمية المجتمعية -- التشريعات السماوية -- العالم الإسلامي